THE ROLE OF EMPLOYEE PERFORMANCE IN MEDIATING THE INFLUENCE OF EMPLOYEE MOTIVATION AND COMPETENCE ON THE EFFECTIVENESS OF HALAL CERTIFICATION SERVICES - Diana Sarah Lubis; Adelina Lubis; Ikbar Pratama (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study aims to determine the influence of employee motivation and competence on the effectiveness of halal certification services through employee performance as an intervening variable at the Medan City Ministry of Religious Affairs Office. This quantitative study used the Structural Equation Modeling Partial Least Square (SEM-PLS) method with the SmartPLS 4.1.1.4 application to examine the relationship between motivation, employee competence, the effectiveness of halal certification services, and employee performance, both directly and indirectly. This study used primary data obtained using a research questionnaire. Seventy-two respondents, consisting of employees at the Medan City Ministry of Religious Affairs Office, were recruited using the Slovin sampling technique. The results of the hypothesis test indicate that employee motivation and competence directly have a positive effect on employee performance, with a path coefficient of 0.386 and a t-statistic of 3.170, and a t-statistic of 0.528 and a t-statistic of 4.187. Employee performance positively influences the effectiveness of halal certification services, with a path coefficient of 0.391 and a t-statistic of 2.073. Directly, employee motivation and competence positively influence the effectiveness of halal certification services, with a path coefficient of 0.399 and a t-statistic of 2.678, respectively, and 0.421 and a t-statistic of 2.188. Indirectly, employee motivation and competence positively influence the effectiveness of halal certification services through employee performance, with a path coefficient of 0.151 and a t-statistic of 1.598, and 0.207 and a t-statistic of 1.895.